Functionalised Au Coated Iron Oxide Nanocomposites Based Reusable Immunosensor for AFB1 Detection. (11th October 2015) - Chauhan, Ruchika; Basu, T.
Abstract : A reusable sandwiched electrochemical piezoelectric immunosensor has been developed for aflatoxin B1 (AFB1) detection using gold coated iron oxide core-shell (Au-Fe3 O4 ) nanostructure. The monoclonal anti-aflatoxin antibody (aAFB1) was immobilized on self-assembled monolayer of 4-aminothiophenol on gold coated quartz crystal to fabricate immunoelectrode (BSA/aAFB1/4-ATP/Au). In addition, secondary rabbit-immunoglobulin antibodies (r-IgGs) functionalized with Au-Fe3 O4 NPs via cysteamine (r-IgG-Cys-Au-Fe3 O4 ) were allowed to interact with AFB1. Both competitive and noncompetitive strategies were employed and a competition between coated AFB1 and free AFB1 was carried out. The competitive mode shows higher linear range (0.05 to 5 ng mL −1 ) than the noncompetitive one (0.5 to 5 ng mL −1 ), high sensitivity 335.7 µ A ng −1 mL cm −2, and LOD 0.07 ng mL −1 . The fabricated immunosensor has been tested using cereal samples spiked with different concentrations of AFB1. The developed competitive immunoelectrode displays good reproducibility, and storage stability and regenerated with negligible loss in activity through removal of the r-IgG-Cys-Au-Fe3 O4 conjugate using a strong external magnet.